The landscape of economic growth do middle income countries differ?. - Eichengreen, Barry (Metro Manila, Philippines Asian Development Bank, 2017)
A review of the growth experience of middle income countries suggests that economic factors associated with growth appear to differ between middle income and other countries. Demographic variables also matter importantly in low income countries. In middle income countries, in contrast, measures of the financial system no longer appear to matter as importantly, as if inefficiencies in banking and financial systems are no longer as binding a constraint as at earlier stages of financial development; nor are demographic variables as important as before. At this point, other variables gain a growing role: these include whether the country experiences a banking or currency crisis, the extent of nonforeign direct investment capital inflows, and government debt as a share of gross domestic product.
Keywords: Economic development; Energy policy, Economics and management; Electronic books